Perlindungan Hukum Terhadap Konsumen Melalui Sertifikasi Halal pada Produk Obat-obatan Berdasarkan Undang- Undang No 33 Tahun 2014 tentang Jaminan Produk Halal - lsye Aprilia; Ni Luh Made Mahendrawati; Ni Made Jaya Senastri (Warmadewa Press, 2021)
Medicines must have halal certification to ensure the halalness of the product. Article 4 of the Law on Halal Product Guarantee, stipulates that all products circulating in Indonesia must be certified halal. In fact, many medicinal products are already circulating in the community but do not yet have a halal certificate. So this raises legal problems related to consumer protection. The purpose of this research is to reveal the authority of related institutions in halal certification of medicinal products circulating in Indonesia as well as legal protection for consumers if a medicinal product that has been disseminated has a halal label even though it does not have a halal label. This study uses a normative legal research method with a conceptual approach and legislation. The source of legal material in this study is the primary and secondary legal materials. The technique of collecting legal materials by analyzing and quoting applicable laws from books, literature, and other sources. The results showed that with the establishment of the Halal Product Guarantee Organizer, the halal regulation of drugs circulating in Indonesia is subject to the Halal Product Guarantee Law No. 33 of 2014 which regulates that certification and labeling of halal products is mandatory. If business actors violate their obligations under these regulations, they will be subject to administrative sanctions in the form of written warnings, administrative fines, and suspension of halal certification.